Transcriptome analysis reveals rootstock-driven effects on growth and photosynthesis in Camellia chekiangoleosa: A phenotypic and biochemical perspective - Zexin Chen; Linqing Cao; Chuansong Chen; Qiuping Zhong; Tieding He; Jinfeng Wang; Youcheng Zhou; Yuling Zou; Xiaoning Ge (PLoS ONE, 2025)
Camellia chekiangoleosa is a significant oil-bearing tree species, known for its high oleic acid content and shorter reproductive cycle compared to traditional oil-tea plants. However, there are few studies on the molecular mechanism and compatibility of the interaction between oil-Camellia scion and rootstock, which poses certain challenges to the cultivation and promotion of oil-Camellia. This study systematically evaluates the effects of hetero-grafting Camellia chekiangoleosa scions onto divergent rootstocks (Camellia chekiangoleosa, Camellia oleifera, and Camellia yuhsienensis). Then the research investigates how rootstock selection alters scion growth and development through phenotypic, biochemical, and transcriptomic analyses. Our findings reveal that the combination of C. oleifera scion grafted onto C. yuhsienensis suppresses auxin (IAA) and cytokinin (ZR) levels while elevating abscisic acid (ABA). Transcriptomic analysis identified that the PYL1, AMY, and INV1 screened by transcriptome data were mainly enriched in starch and sucrose metabolic pathways and plant hormone signal transduction, which collectively prioritize carbon allocation toward growth over storage. Meanwhile, hetero-grafting improved photosynthetic capacity by upregulating light-harvesting complex (LHC) genes and carotenoid biosynthesis enzymes (ZEP), optimizing light energy conversion and photoprotection. These findings provide novel insights into the molecular mechanisms underlying rootstock-scion interactions in oil-Camellia, bridging a critical knowledge gap in this economically important genus.